Acceptance Analysis of AIRA Mobile Banking Application Using the Technology Acceptance Model (TAM) - Prasetyo Indra Surono; Sri Wahyuni (Universitas KH. Abdul Chalim Mojokerto, 2026)
The primary objective of this research is to evaluate how users adopt the AIRA Mobile banking platform frameworked by the Technology Acceptance Model (TAM). Methodologically, an explanatory quantitative design integrated with a verificative approach was adopted. The population in this study comprises 7,134 users of AIRA Mobile banking at Nanobank Syariah Balikpapan Branch, based on data as of December 31, 2025. Purposive sampling was chosen as the sampling method. Data collection utilized a Google Form distributed via links through WhatsApp. To process the collected data, structural equation modeling via the Partial Least Squares (PLS) technique was executed through SmartPLS 3 software. The empirical findings reveal that Innovativeness significantly and positively drives both Perceived Usefulness and Perceived Ease of Use in the use of Aira Mobile. Furthermore, Perceived Ease of Use exerts a meaningful positive impact on Perceived Usefulness as well as Attitude Toward Using. The data also confirms that Perceived Usefulness substantially enhances Attitude Toward Using. Ultimately, both Perceived Usefulness and Attitude Toward Using are proven to have a significant positive bearing on consumers' Behavioral Intention to continue utilizing the application in the use of Aira Mobile.